Assessment in the visual arts: Challenges and possibilities. Issue 3 (3rd July 2019) - Graham, Mark
Abstract: Assessment in art is notoriously difficult and is probably best approached with skepticism. Artistry is notoriously difficult to assess. Yet measures of student learning in art are needed for both advocacy and art education policy. Assessments, particularly large-scale assessments, influence funding and educational policy at all levels. This article explores some of the challenges of assessment in the visual arts and critically examines the Advanced Placement Studio Art Portfolio to illustrate how a product-oriented assessment might influence teaching and policy.